Investigation of the Relationship Between Tumor Microenvironment and Prognostic Parameters in Invasive Breast Carcinomas of No Special Type: A Retrospective Analysis - Mine OZSEN; Sahsine TOLUNAY; Kazim SENOL; Adem DELIGONUL; Sehsuvar GOKGOZ; Turkkan EVRENSEL (Federation of Turkish Pathology Societies, 2024)
Objective: The tumor microenvironment is a heterogeneous and constantly changing territory that plays an active role in tumor formation and progression. It constantly interacts with tumor cells, plays an active role in tumor development, and even appears as a parameter of prognostic importance, and the importance of the tumor microenvironment in breast cancer has been emphasized by recent studies. In this study, we aimed to retrospectively evaluate the relationship between the tumor microenvironment and prognostic parameters in invasive breast carcinomas of no special type. Material and Methods: A total of 271 cases diagnosed as invasive breast carcinoma of no special type from resection materials in our center between 2007 and 2015 were included in the study. Hematoxylin-eosin stained slides with a thickness of 4-5 micrometers were evaluated in terms of tumor infiltrating lymphocytes, peritumoral and intratumoral desmoplastic reaction, intratumoral and peritumoral tumor budding, stromal features, and tumor growth pattern. Results: When parameters related to the tumor microenvironment were compared with other prognostic parameters, there was a significant relationship between TILs and tumor grade, size, stage, immunohistochemical subgroup and Ki-67 proliferation index. A significant relationship was detected between intratumoral stromal reaction and tumor grade, size, molecular subgroup and the Ki-67 proliferation index (p<0.05). When stroma and other prognostic parameters were compared, tumors with desmoplastic stroma had higher grades and higher Ki-67 proliferation indexes, and they were observed more frequently in the triple negative molecular subgroup. Conclusion: We believe that including parameters related to tumor microenvironment in breast cancer reports, which hold a prognostic and predictive importance, will contribute to patient management. Considering the fact that these can be easily evaluated from routinely used hematoxylin-eosin stained slides, this does not cause additional costs or excessive time loss.